Implementación de un módulo didáctico para determinar la resistencia mecánica de los materiales para el laboratorio de la Universidad Técnica de Cotopaxi Extensión La Maná. - Cañizares Macias, Alexander Mesias (2023)
The main objective of this research work is to build a teaching module for the analysis of the mechanical resistance of materials, with the purpose of providing students with a tool to be able to apply the concepts learned in the classroom by carrying out practices. For the construction of the module, bibliographic research was carried out, the teaching module is built through a hydraulic system and for the structure we use materials and elements such as: round steel bar, steel plates, hydraulic pump, hydraulic valves, hydraulic cylinder , pressure hoses, filters, electric motor and a reservoir for hydraulic fluid. The design of the teaching module was carried out using machine design software which used the simulation system by the finite element method, and thus be able to choose the appropriate materials for the manufacture of the module. The results obtained in this investigation were as expected; destructive tensile tests were carried out on a metallic material which, when the necessary force was applied, reached its breaking point. The module was designed based on the universal testing machine and we managed to obtain the same results by conducting tests.